An observational study investigating the use of patient-owned technology to quantify physical activity in survivors of critical illness. Issue 2 (March 2020) - Gluck, Samuel; Summers, Matthew James; Finnis, Mark Edward; Andrawos, Alice; Goddard, Thomas Paul; Hodgson, Carol Lynette; Iwashyna, Theodore John; Deane, Adam Michael
Abstract: Background: Physical activity after intensive care unit (ICU) discharge is challenging to measure but could inform research and practice. A patient's smartphone may provide a novel method to quantify physical activity. Objectives: We aimed to evaluate the feasibility and accuracy of using smartphone step counts among survivors of critical illness. Methods: We performed a prospective observational cohort study in 50 patients who had an ICU length of stay>48 h, owned a smartphone, were ambulatory before admission, and were likely to attend follow-up at 3 and 6 months after discharge. At follow-up, daily step counts were extracted from participants' smartphones and two FitBit pedometers, and exercise capacity (6-min walk test) and quality of life (European Quality of Life-5 Dimensions) were measured. Results: Thirty-nine (78%) patients returned at 3 months and 33 (66%) at 6 months, the median [interquartile range] smartphone step counts being 3372 [1688–5899] and 2716 [1717–5994], respectively. There was a strong linear relationship, with smartphone approximating 0.71 (0.58, 0.84) of FitBit step counts, P < 0.0001, R-squared = 0.87. There were weak relationships between step counts and the 6-min walk test distance. Conclusion: Although smartphone ownership and data acquisition limit the viability of using extracted smartphone steps at this time, mean daily step counts recorded using a smartphone may act as a surrogate for a dedicated pedometer; however, the relationship between step counts and other measures of physical recovery remains unclear.